2022
DOI: 10.1002/wps.20938
|View full text |Cite
|
Sign up to set email alerts
|

Designing and scaling up integrated youth mental health care

Abstract: Mental ill‐health represents the main threat to the health, survival and future potential of young people around the world. There are indications that this is a rising tide of vulnerability and need for care, a trend that has been augmented by the COVID‐19 pandemic. It represents a global public health crisis, which not only demands a deep and sophisticated understanding of possible targets for prevention, but also urgent reform and investment in the provision of developmentally appropriate clinical care. Desp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
193
0
9

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 284 publications
(205 citation statements)
references
References 141 publications
(158 reference statements)
3
193
0
9
Order By: Relevance
“…Furthermore, in Denmark's educational institutes, students are directed to learn the course material in groups to reach a significant conclusion through discussion and appropriate learning ( 38 ). Although students' critical thinking abilities develop to an advanced level, they are also effectively working when they are instructed to learn and draw a conclusion based on any project provided for group discussion ( 39 ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, in Denmark's educational institutes, students are directed to learn the course material in groups to reach a significant conclusion through discussion and appropriate learning ( 38 ). Although students' critical thinking abilities develop to an advanced level, they are also effectively working when they are instructed to learn and draw a conclusion based on any project provided for group discussion ( 39 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In comparison, if the students are not tolerating the opponent's lives when working on the project-based learning material in the group, then it would not be appropriate for them to develop their concepts effectively related to their course material and the effectiveness of the information sharing in the group. Furthermore, in Denmark's educational institutes, students are directed to learn the course material in groups to reach a significant conclusion through discussion and appropriate learning (38). Although students' critical thinking abilities develop to an advanced level, they are also effectively working when they are instructed to learn and draw a conclusion based on any project provided for group discussion (39).…”
Section: Mental Health Project-based Learning and Learning Performancementioning
confidence: 99%
“…The evidence is also compelling that young people, in particular, need to be the target population for early intervention since many mental disorders onset occurs in this period and are most affected by the pandemic. 20,30 A pragmatic trial by Anjara et al 31 showed that primary care staff could provide mental health care for common mental disorders with a comparable result with a specialist, given proper training and support. Another interesting trial in Indonesia by Arjadi et al, 32 who used internet intervention (a web-based therapy on the behavioral activation principle) to address depression in the community, also supports the task-sharing approach.…”
Section: Pandemic Young People and Increasing Awareness Of Mental Healthmentioning
confidence: 99%
“…Discrepant reports between these different informants not only reveal different perspectives and priorities [ 11 ] but can also convey information about the different contexts in which mental health difficulties are most manifested [ 12 ]. Finally, the inclusion of youth voices is a core principle of an ongoing transformative movement towards more person-centred and youth-friendly models of mental health care [ 13 , 14 ]. It is therefore of paramount importance to ensure that the voices of children and adolescents are centred in the measurement of mental health concerns and outcomes, enabling them to have appropriate understanding, involvement, and empowerment in their care [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%